Fluctuating saline conditions favor competition of Bolboschoenus planiculmis, a dominant species in inland salt marshes - Wang, Lingxi; Zhang, Hongxiang; Tao, Yitong; Zhang, Tao; Li, Xiaoqing; Yu, Xiaoqian; Yan, An; He, Chunguang; Zheng, Wei; Gao, Yingzhi (Ecological processes, 2025)
Background The changing hydrological conditions in wetland ecosystems are often accompanied by salt fluctuations. However, how fluctuating salt conditions affect growth and interspecific competition of dominant plants in wetlands remains unclear. This study aims to investigate the response of growth and competitive ability of a dominant species in inland salt marshes, Bolboschoenus planiculmis , under different salt conditions and test if B. planiculmis is more adapted to the fluctuating salt environments. Methods We quantified the growth indices and competitive response of B. planiculmis and two other dominant species Phragmites australis and Suaeda salsa under five salt treatments (control, constant NaCl, constant mixed salt, pulsed increase of mixed salt, and fixed increase of mixed salt) and two competition treatments (no competition and interspecific competition) in a greenhouse experiment. Results We found that the total biomass of B. planiculmis was significantly higher under the mixed salt treatments compared to the NaCl treatment, and was more advantageous than S. salsa in the mixed salt treatments when competing with it . Fluctuating mixed salt treatments significantly increased the total biomass of B. planiculmis more than the constant mixed salt treatment. Particularly, B. planiculmis benefited more than P. australis or S. salsa in competition. Moreover, the competitive response of B. planiculmis was stronger than the other two species in the fluctuating mixed salt treatments, although the biomass of B. planiculmis was lower than the other two species. Conclusion Our results demonstrated that fluctuating salt conditions prioritized interspecific competition of B. planiculmis. We support the competition-to-stress hypothesis that the competition ability rather than salt stress tolerance was the main determinant of species survival in fluctuating salt with a less stressful survival condition. Our study provides important information in understanding community composition changes and restoration of degraded salt marshes.